2023
DOI: 10.1186/s13075-023-03090-y
|View full text |Cite|
|
Sign up to set email alerts
|

Learnings from clinical trials in patients with connective tissue disease-associated interstitial lung disease

Abstract: Many clinical trial results are available to inform best practices in the treatment of patients with connective tissue disease-associated interstitial lung disease (CTD-ILD).Herein, we summarize the results of clinical trials, including patient-reported outcome instruments, for the treatment of patients with ILD associated with systemic sclerosis (SSc/scleroderma), rheumatoid arthritis, and idiopathic inflammatory myositis, the diseases with the most available data. For SSc-ILD, the US Food and Drug Administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Following publication of the original article [ 1 ], the authors identified an error to Jean Paul Higuero Sevilla’s last name. The correct last name should be “Higuero Sevilla” instead of “Sevilla”.…”
mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error to Jean Paul Higuero Sevilla’s last name. The correct last name should be “Higuero Sevilla” instead of “Sevilla”.…”
mentioning
confidence: 99%